Seasonal variation of nutritional constituents in fish of South Asian Countries: A review - Rasul, Md Golam; Jahan, Israt; Yuan, Chunhong; Sarkar, Md Shirajul Islam; Bapary, Mohammad Abu Jafor; Baten, Md Abdul; Shah, A K M Azad (Fundamental and Applied Agriculture, 2021)
Knowledge of the changes of essential nutritional constituents (i.e. moisture, protein, lipid, minerals, amino acid and fatty acid profile) of fish with sea- sons is indispensable to estimate their energy value and to plan the most appropriate industrial and commercial processing. This article reviewed the nutritional constituents of 28 different fish species of Bangladesh and other South Asian countries like India, Pakistan in three different seasons viz. pre-monsoon (April-June), monsoon (August-October) and post-monsoon (December-February). Available findings have shown that proximate com- position, amino acid and fatty acid profile varied in accordance to changes of the seasons. As the environmental factors including water temperature, pH, salinity and food availability changes with the seasons, which in turn influence the amino acid and fatty acid profile of fish in different season. Moisture content known to vary in some fishes for maintaining osmoregu- lation during migration. This phenomenon also largely affects the seasonal variation of proximate composition of fish. In addition, age, size, sex, habitat, breeding season and starvation during migration are also known to diverge the nutritional composition of fish in different seasons. It is generally view that fish utilizes lipid as energy source in different seasonal circumstances as gonadal development, maturation, spawning or migration and there is an in- verse relationship between lipid and moisture content. Protein, lipid, amino acids and saturated fatty acid concentration were comparatively higher in pre-monsoon and lower in post-monsoon, whereas monounsaturated fatty acids and polyunsaturated fatty acids were higher in post-monsoon season in many of the fishes; attributed to gonadal development of fish, when it mi- grates a long way. Finally, this review might help to understand the changes in nutritional values of some commercial fishes in various seasons and will assist in identifying the proper fish harvesting period.